Time to Response in Panic Disorder in a Naturalistic Setting: Combination Therapy with Alprazolam Orally Disintegrating Tablets and Serotonin Reuptake Inhibitors Compared to Serotonin Reuptake Inhibitors Alone - Katzelnick, David J. (Matrix Medical Communications, 2006)
Objective: This study evaluated time to response in the treatment of panic disorder with a selective serotonin reuptake inhibitor (SSRI) or serotonin norepinephrine reuptake inhibitor (SNRI) combined with alprazolam orally disintegrating tablets (ODT), or SSRI/SNRI alone. Design: Subjects were randomized to eight weeks open-label treatment with alprazolam ODT (4 weeks treatment followed by 3–4 week taper) combined with an SSRI or SNRI, or treatment with SSRI/SNRI alone. Setting: The study was conducted under naturalistic conditions at 62 primary care and 34 psychiatric practices. Participants: Male or female subjects ≥18 years of age diagnosed with panic disorder, with or without agoraphobia. Measurements: The primary efficacy measure was time to response, defined as ≥50-percent decrease from baseline Hamilton Rating Scale for Anxiety (HAM-A) total score. Secondary measures included change from baseline in HAM-A scores and the Clinical Global Impression of Improvement (CGI-I) and Patient Global Impression (PGI) scales. Results: The intent-to-treat (ITT) population comprised 245 subjects. There was no statistical difference between treatment groups in time to response in the ITT population; however, a prospectively defined per protocol analysis revealed a statistically significant earlier onset of effect in subjects receiving SSRI/SNRI plus alprazolam ODT (P<0.05). Mean change from baseline in HAM-A total score and clinician and patient measures of global improvement also showed statistically significant early advantages for combination therapy compared with SSRI/SNRI monotherapy. Conclusion: Combined treatment of panic disorder with alprazolam ODT and an SSRI/SNRI may be associated with more rapid improvement in anxiety symptoms compared with an SSRI/SNRI alone.